Signal Detection Based on Particle Swarm Optimization for MIMO-OFDM System - ChaoQun Wu; Dan Zhao; JingPeng Gao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to overcome the defects of the slow convergence rate of the traditional Genetic Algorithm and basic Particle Swarm Optimization drops into local optimum easily, an improved Particle Swarm Optimization algorithm based on hybrid algorithm is proposed and applied to the signal detection for MIMO-OFDM system. The algorithm optimizes the basic Particle Swarm Optimization algorithm and some problems were solved by means of Particle Swarm Optimization combined with Genetic Algorithm for signal detection. Through the theoretical analysis and the simulation research, this improved algorithm is superior to basic Particle Swarm Optimization algorithm 0.5dB under the same number of iterations and is better than traditional Genetic Algorithm 0.5dB under the same bit error rate. This algorithm improves the system signal detection performance effectively with less iteration and reduces the bit error rate. It has rapid speed of convergence and strong capability of global search. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5105